To report a case of crystalline keratopathy induced by Dieffenbachia plant sap and literature review - BAĞATUR VURGUN, ELİF; ARSLAN, SILA CANSU; TOKER, AYŞE EBRU; Akkaya Turhan, Semra (My University, 2022)
© 2022 The AuthorsPurpose: To report a case of crystalline keratopathy induced the Dieffenbachia plant sap. Methods: Case report and review of the literature. Results: A 38-year-old woman presented with redness, irritation, and slightly blurred vision in the right eye after the exposure of Dieffenbachia plant sap to her right eye. The patient\"s eye was irrigated with copious saline on her admission. On ophthalmic examination, her visual acuity was 20/32 OD and 20/20 OS. Anterior segment examination of the right eye revealed mild eyelid edema, grade 2 conjunctival hyperemia, diffuse punctate corneal epithelial erosions, mild stromal edema, and fine refractile needle-like crystals extending from the subepithelial region to mid-stroma. The crystals were visualized with anterior segment photographs and in vivo corneal confocal microscopy (IVCCM) views. Moxifloxacin 0.5% and preservative-free artificial tears were started. Loteprednol etabonate 0.5% was added once the epithelial erosions had healed. The corneal crystals were completely disappeared and the visual acuity of the patient was 20/20 in the third week\"s visit. Conclusions: Patients with a history of contact with plant sap should be irrigated with abundant saline immediately to reduce the effect of chemical trauma and thus reduce mechanical damage by inhibiting crystal penetration. IVCCM offers a non-invasive, fast, and reliable diagnosis of Dieffenbachia-related injury, especially in patients with ocular irritation of unknown etiology. Besides, IVCCM is very valuable to differentiate calcium oxalate crystals from other crystalline corneopathies.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Medicine; Health Sciences; Surgery Medicine Sciences; Eye Diseases and Surgery; Klinik Tıp (MED); Klinik Tıp; GÖZ HASTALIKLARI; Clinical Medicine (MED); CLINICAL MEDICINE; OPHTHALMOLOGY; Oftalmoloji; Ophthalmology; Crystalline keratopathy; Dieffenbachia; In vivo corneal confocal microscopy